Neuroprotective Effect of Dexmeditomidinein Patients with TraumaticBrain Injury Using Interleukin-6 As Inflammatory Marker: Review Article - Asmaa Mohamed Aly; Ibrahim Abbas Yousef; Haidy Salah Mansour; Mokhtar Mostafa Mahran (International Journal of Medical Toxicology and Legal Medicine, 2024)
Synopsis: Research on the role of dexmedetomidine in neonatology and anesthesia has been particularly interesting since the drug's many benefits were reported (1). These benefits include improving post-operative recovery, lowering the need for opioids, lowering sympathetic tone, preventing inflammatory reactions, and safeguarding organs (1). This review article aims to evaluate the effectiveness of dexmedetomidine in causing neuroprotection in individuals with head trauma